Functional Study of Haplotypes in UGT1A1 Promoter to Find a Novel Genetic Variant Leading to Reduced Gene Expression. Issue 3 (June 2015) - Shin, Hee Jung; Kim, Jason Yongha; Cheong, Hyun Sub; Na, Han Sung; Shin, Hyoung Doo; Chung, Myeon Woo
<x xml:space="preserve">Abstract</x> Background: Uridine diphosphate glucuronyltransferase 1 family, A1 (UGT1A1) encodes for an enzyme that is a part of glucuronidation pathway, and a number of studies have shown that the promoter polymorphisms of UGT1A1 are associated with various diseases and drug response. In this study, we examined a possible association between UGT1A1 promoter haplotypes and the gene expression level. Methods: To identify promoter haplotype structure population, we directly sequenced the promoter region of UGT1A1 in 192 healthy Korean to identify 10 UGT1A1 promoter single-nucleotide polymorphisms (SNPs). Then, we genotyped the 10 SNPs in additional 192 non-Korean samples comprised of Chinese, Japanese, European American, and African American, and constructed haplotype structures. Furthermore, we conducted luciferase assay for the promoter SNP haplotypes to examine a possible expression change. Results: rs3755319C—rs2003569A—rs887829C—rs8175347(TA)6 (6.60 ± 0.15) and rs3755319A—rs2003569 G—rs887829C–rs8175347(TA)7 (2.79 ± 0.97) led to significantly lower gene expression when compared with rs3755319C—rs2003569 G—rs887829T—rs8175347(TA)6 (8.28 ± 0.60). Conclusions: Our result suggests that the haplotypes in UGT1A1 promoter region can affect the expression level of the gene and drug metabolism associated with UGT1A1. Furthermore, in addition to rs8175347, rs3755319 was found to induce lower gene expression of UGT1A1.